2021
DOI: 10.1021/acscatal.1c03574
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Insights into Cl-Triggered Highly Selective Ethylene Electrochemical Oxidation to Epoxide on RuO2: Unexpected Role of the In Situ Generated Intermediate to Achieve Active Site Isolation

Abstract: Electrochemical partial oxidation of hydrocarbons to value-added products using electricity from renewable energy resources has the potential to change the way that commodity chemicals are manufactured. In this study, we used density functional theory calculations combined with a constant electrode potential model to study the previously reported ethylene partial electro-oxidation to epoxide on RuO2(110) in an aqueous solution containing [Cl–] = 0.3 M. We found that the high selectivity toward epoxide is due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…52 The details regarding how to correct the electronic energy due to an electron being added to or removed from the system and how to construct free energy surfaces can be found in the Supporting Information (SI) or our previous works. 53,54 This approach has been used by our group 5,53−58 and others 59−66 to study a variety of electrochemical reactions. Some recent theoretical studies have suggested that better thermodynamics of overall electrochemical reactions can be achieved by correcting the computed free energies of the gas molecules involved in the reactions.…”
Section: Pbe-d3mentioning
confidence: 99%
See 1 more Smart Citation
“…52 The details regarding how to correct the electronic energy due to an electron being added to or removed from the system and how to construct free energy surfaces can be found in the Supporting Information (SI) or our previous works. 53,54 This approach has been used by our group 5,53−58 and others 59−66 to study a variety of electrochemical reactions. Some recent theoretical studies have suggested that better thermodynamics of overall electrochemical reactions can be achieved by correcting the computed free energies of the gas molecules involved in the reactions.…”
Section: Pbe-d3mentioning
confidence: 99%
“…The linear Poisson–Boltzmann implicit solvation model as implemented in VASPsol with a Debye screening length of 3.0 Å was utilized to simulate water (dielectric constant = 78.4) and the electrolyte and maintain the neutrality of the simulation cell . The details regarding how to correct the electronic energy due to an electron being added to or removed from the system and how to construct free energy surfaces can be found in the Supporting Information (SI) or our previous works. , This approach has been used by our group , and others to study a variety of electrochemical reactions. Some recent theoretical studies have suggested that better thermodynamics of overall electrochemical reactions can be achieved by correcting the computed free energies of the gas molecules involved in the reactions. We found that applying the correction suggested by Calle-Vallejo and co-workers to CO 2 , which is the only molecule in the current system, leads to no change in our major conclusions (Table S2).…”
Section: Computational Detailsmentioning
confidence: 99%
“…The electrocatalytic ethylene oxidation reaction (C 2 H 4 OR) has long been investigated to synthesize ethylene oxide [18–20] and ethylene glycol, [21] but typically with low Faradaic efficiencies (FEs). In such an electrochemical process, the *O intermediate generated in anodic oxygen evolution reaction (OER) can break C=C double bond and produce ethylene glycol, while it is easy to be over‐oxidized to CO or CO 2 [18–20] . Recently, Sargent and co‐workers combined chlorine evolution reaction (ClER) to promote C 2 H 4 OR into 2‐chloroethanol and ethylene oxide with improved current densities and single‐pass conversion rates [22, 23] …”
Section: Introductionmentioning
confidence: 99%
“…C 2 H 4 is one of the most important feedstocks used in chemical industry for manufacturing a variety of downstream products. [16,17] The electrocatalytic ethylene oxidation reaction (C 2 H 4 OR) has long been investigated to synthesize ethylene oxide [18][19][20] and ethylene glycol, [21] but typically with low Faradaic efficiencies (FEs). In such an electrochemical process, the *O intermediate generated in anodic oxygen evolution reaction (OER) can break C=C double bond and produce ethylene glycol, while it is easy to be over-oxidized to CO or CO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation